THE INFLUENCE OF PERSONAL SELLING ACTIVITIES DECISION TO PURCHASE PUCUK HARUM TEA BEVERAGE PRODUCTS - Amelia Nugraeni (Publikasi Inspirasi Indonesia, 2023)
This research aims to analyze the influence of personal selling activities on consumer purchasing decisions for Teh Pucuk Harum beverage products. The research was carried out using a qualitative approach by collecting data through interviews with consumers and analysis of documents related to sales activities. The research results show that personal selling activities have a significant positive impact on consumer purchasing decisions. Direct interactions between sellers and consumers help increase product awareness, build trust, and influence consumers' decision-making processes. Sellers who have in-depth knowledge about the product and are able to answer consumer questions satisfactorily can increase consumer confidence in Pucuk Harum Tea. Apart from that, personal selling activities also have an important role in overcoming consumer doubts or concerns, thereby smoothing the purchasing process. Consumers who experience positive interactions with sellers tend to be more loyal and have a tendency to buy Teh Pucuk Harum again in the future. However, this research also identified several challenges faced in implementing personal selling activities, including consistency in message delivery and increasing seller competency. The results of this research provide valuable insight for companies in optimizing personal selling strategies to increase sales and build long-term relationships with consumers.